Alleviation of Myocardial Inflammation in Diabetic Rats by Flavonoid Extract of Helichrysum Arenarium and Its Effect on Damaged Myocardial Cells Induced by High Glucose - Liu, Huanyu; Lan, Wei (Frontiers in Surgery, 2022)
To investigate the effects of helichrysum arenarium flavonoid extract on high glucose damaged cardiomyocytes and the alleviation of myocardial inflammation in diabetic rats. The study was divided into two parts, the first part was a cellular experiment in which a high-glucose cardiomyocyte injury model (H9C2) was established using a high-glucose culture medium, divided into low, medium and high dose groups of helichrysum arenarium intervention and a model control group. The levels of enzyme activities [creatine kinase (CK) and lactate dehydrogenase (LDH)] in each group of H9c2 cells were measured by ELISA, the expression levels of apoptotic proteins (Bax and Bcl-2) by protein blotting (WB), and the expression levels of inflammatory factors (TNF-α, IL-1β, IL-6) by RT-qPCR. The second part is animal experiments, after establishing the diabetic rat model, we used helichrysum arenarium flavonoid extract to intervene SD rats, divided into helichrysum arenarium intervention low, medium and high dose groups, SD rat model group. HE staining was used to observe myocardial tissue lesions, and RT-qPCR method was used to detect inflammatory (TNF-α, IL-1β, IL-6) infiltration in myocardial tissue. The results showed that the helichrysum arenarium flavonoid extract can reduce the degree of damage of H9C2 cells induced by high glucose and decrease the cellular inflammatory response, and its mechanism of action may be achieved by regulating the apoptotic factors Bax and Bcl-2. In addition, the extract of helichrysum arenarium can reduce the histopathological damage of myocardium in diabetic rats, decrease the inflammatory response in the tissue, and achieve the effect of myocardial protection.